Revision of the subgenus Acanthosia Krüger, 2015 in the genus Archithosia Birket-Smith, 1965, with a description of four new species (Lepidoptera: Erebidae: Arctiinae: Lithosiini) - Durante, Antonio; Potenza, Luigi; Pellegrino, Gabriele (Zootaxa, 2025)
The subgenus Acanthosia Krüger, 2015 of the genus Archithosia Birket-Smith, 1965 is revised. two species are recorded for the first time in Gabon: A. flavifrontella (Strand, 1912) and A. similis Birket-Smith, 1965; two new species groups are proposed: A. flavifrontella (Strand, 1912) species group and A. tryphosa (Kiriakoff, 1958) species group; and three species are described as new: Archithosia (Acanthosia) oblonga sp. nov.; A. (A.) brevis sp. nov. and A. (A.) parva sp. nov. A teratological specimen of A. flavifrontella is also recorded.